Instant Tiwul Formulation High in Antioxidants from Mocaf Flour and Okra Flour: Formulasi Tiwul Instan Tinggi Antioksidan dari Tepung Mocaf dan Tepung Okra - Nofiyanto, Erwin; Wahyuningsih, Sri Budi; Tatarina, Siska (Universitas Slamet Riyadi Surakarta, 2024)
Tiwul is a traditional food source of carbohydrates made from traditionally processed cassava, which is used as a substitute for rice. This research aimed to determine the effect of adding mocaf flour and okra flour (Abelmoschus esculentus) on the chemical and antioxidant properties of instant tiwul. The research method used an experimental design, namely a one-factor Completely Randomized Design (CRD), with treatment comparison between mocaf flour and okra flour (100:0, 85:15, 75:25, 65:35). Each treatment was repeated 4 times. The variables observed were air content, ash, fat, protein, carbohydrates, antioxidants, and preference tests. The data obtained was described as diverse, and if there were differences between treatments, then it was tested further using the Duncan Multiple Range Test (DMRT) at the 5% level. The research results of instant tiwul with the addition of 85% mocaf flour and 15% okra flour formulation were instant tiwul with the best treatment in chemical testing and liked by consumers. The selected instant tiwul had an air content of 2.46%, ash content of 2.05%, fat content of 0.32%, protein content of 3.93%, carbohydrates of 81.25%, and antioxidant activity of 81.25%. The tiwul formulation from mocaf flour and okra flour can fulfill the requirements for instant tiwul.